Early weaning modulates eating behavior and promotes hypofunction of the serotonergic (5HT) system in juvenile male rats. Issue 3 (9th March 2020) - Tavares, Gabriel Araújo; do Amaral Almeida, Larissa Cavalcanti; de Souza, Julliet Araújo; de Souza, Felipe Leitão; Feitosa Braz, Glauber Rudá; Silva, Bruna Times; da Silva Santos, Andresa Mayara; Lagranha, Cláudia Jacques; de Souza, Sandra Lopes
Abstract: Early life stress (ELS) has been associated with developmental impairments. Early weaning (EW) is a postnatal stress model consisting of interruption of lactation and maternal care. The 5HT‐system has been associated with neurobehavioral modulations promoted by ELS. Thus, the present work aims to investigate the effects of early weaning on feeding behavior and serotonergic system of juvenile male rats. For this, rats were submitted to early (PND15) or natural (PND30) weaning and had the body weight, food intake in circadian phases, and food intake in response to fenfluramine assessed. mRNA expression of serotoninergic receptors (5HT1A and 5HT2C) and transporter (SERT) was assessed in the hypothalamus and brainstem, as well as NPY and POMC mRNA expression in hypothalamus. The results show that early weaning promoted changes in the percentage of weight gain during lactation period and increase in body weight at PND40. It was also observed that EW promoted increase and decrease in food intake in light and dark phase, respectively, and leads to a decreased action of fenfluramine on inhibition of food intake. In addition, early weaning promoted increased NPY and SERT mRNA expression in the hypothalamus and 5HT2C in the brainstem. Together, the data indicate that the stress caused by early weaning impairs the eating behavior of juvenile male rats through hypofunction of the 5HT‐system. Abstract : The aim of this study was to evaluate the effects of early weaning on feeding behavior and serotonin system in male juvenile rats. Rats were submitted to early (PND15) or natural (PND30) weaning and had the feeding behavior and serotonin system evaluated at juvenile age. Early weaning promoted decreased fenfluramine action on inhibition of food intake and increased mRNA expression of SERT and NPY on hypothalamus and 5HT2C on brainstem.